2020
DOI: 10.26487/hjabe.v3i4.378
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Leadership Style and Work Discipline on Service Quality and Employee Performance in the Investment Office and One Stop Integrated Service in Makassar City

Abstract: This study aims to determine the Effect of leadership sale and work discipline on service Quality and Employee Performance in the Investment Office and One-Stop Integrated service in Makassar city. The approach taken in this study was a quantitative approach with the path analysis method. The population in this study are employees at the Department of Investment and one-stop integrated service or the city of Makassar. Data collection techniques used observation, interviews, and questionnaires while data proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It increases employee performance by 32,1%. The result is in line with previous studies reporting the positive effect of emotional intelligence on employee performance (Darman & Adha, 2021;Akhmad et al, 2022). Emotional control plays an important role in one's working process, as the work quality is highly determined by employees' ability to control their emotions in various situations.…”
Section: Resultssupporting
confidence: 92%
“…It increases employee performance by 32,1%. The result is in line with previous studies reporting the positive effect of emotional intelligence on employee performance (Darman & Adha, 2021;Akhmad et al, 2022). Emotional control plays an important role in one's working process, as the work quality is highly determined by employees' ability to control their emotions in various situations.…”
Section: Resultssupporting
confidence: 92%
“…Several previous researchers have examined the factors that affect the performance of DPMPTSP employees in various regions in Indonesia. For instance, organizational culture (Yulianto & Ali, 2017), work motivation (Subriah et al, 2020), and leadership (Rahmat et al, 2020). In addition, the are other factors as well, for instance, work environment (Khaeriah et al, 2020), competence (Khaeriah et al, 2020), job satisfaction (Fitri et al, 2020), training (Fitri et al, 2020;Khaeriah et al, 2020), work discipline (Subriah et al, 2020), and compensation (Wiadnyana et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…They found that performance appraisal and feedback were the indicators of leadership that had the most considerable influence on employee performance. Furthermore, Rahmat et al (2020) found that leaders who have good communication with employees and involve employees in decision-making have the highest average score on employee performance at Makassar's DPMPTSP. Furthermore, to realize the success of public services in the current era of digitalization, talented human resources are needed (Mazurchenko & Maršíková, 2019).…”
Section: Introductionmentioning
confidence: 99%